PENGARUH PEMBELAJARAN PROBLEM POSING TERHADAP KOMUNIKASI MATEMATIKA MAHASISWA - Pujilestari, Pujilestari; Yuntawati, Yuntawati (Media Pendidikan Matematika, 2018)
Type of this research is experimental research which aims to determine the effect of problem posing learning on mathematical communication of students prospective mathematics teacher at IKIP Mataram by calculus I module. This module developed by a problem posing approach that meets the criteria of being feasible, practical, and effective. The experimental design used was the type of Quasi Experimental Design and the design used was Nonequivalent Control Group Design. Data collection instruments included tests of mathematical communication skills, student response questionnaires, and lecturer response questionnaires. Based on the results of the hypothesis test analysis obtained a value with a significantlevel Â or is . So that Â it is rejected and accepted. So it can be concluded that Problem Posing Learning by using problem posing based I calculus module influences student mathematics communication and is effectively used in lectures